LECTURE-GROUNDED CHATGPT-4 TUTOR: ENHANCING ADULT LEARNER ENGAGEMENT IN DISTANCE LEARNING - Howard Kim; Jaehyun Yoon; Seung Man Lee; Sung Min Cho; Yeon Ju Kim; Geontae Noh; Jongwon Lee (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Adult learners in remote university programs often struggle with engagement and satisfaction due to limited real-time interaction and support. This presentation introduces an AI-powered learning tutor that leverages ChatGPT-4 in a context-restricted manner, operating strictly within the instructor’s lecture materials and spoken content. By grounding the AI’s knowledge solely in the course textbooks, slides, transcripts, and other instructor-provided materials, the system delivers domain-specific support that is aligned with the curriculum and instructor’s intent. This controlled knowledge scope is a key innovation: it mitigates the usual pitfalls of generative AI (such as misinformation or irrelevant “hallucinations”) by ensuring answers remain faithful to the course content. The AI tutor functions as a virtual teaching assistant, available 24/7 to answer questions and engage in dialogue about the lecture topics. Adult learners can thus seek help at any time without fear of judgment, asking questions they might hesitate to pose to a human instructor. This on-demand, non-judgmental support has been observed to boost learner confidence and promote deeper exploration of course material. Early classroom deployments of the tutor have yielded increased student engagement and satisfaction: the AI’s ability to hold extended conversations within the bounds of the courseware has enhanced learners’ cognitive engagement and the sense of an instructor presence in remote classes. Learners reported feeling more supported and motivated, and instructors noted students coming to class better prepared. We also discuss the pedagogical implications of constraining an AI tutor’s knowledge scope. This approach empowers educators to maintain content control and uphold academic standards while still harnessing AI’s scalability and responsiveness. Instructors can focus on higher-order mentoring as routine FAQs are handled by the AI, illustrating a new model of human–AI collaboration in education. Our findings highlight that a lecture-grounded ChatGPT-4 tutor can significantly enhance engagement and satisfaction among adult learners in remote settings, offering a promising pathway to more interactive, inclusive, and effective online learning experiences.